Need Analysis Vidio Animasi Pada Materi Adzan Dan Shalat Di Kelas Vll MTs DARUL AMIN Palangka Raya - Ulpah, Mega; Rahmayani, Anita (Tarbawi, 2024)
Abstract The aim of this research is to assess the extent of the efficacy of learning media applied in the learning process and provide constructive recommendations for further development to increase the effectiveness of learning in the future. This research is classified as a quantitative descriptive research type which aims to describe and analyze the use of media in the context of learning material about the call to prayer and prayer. This research was carried out by quantitatively analyzing data obtained through questionnaires distributed to 24 class VII students, which were filled in online using Google Form. The questionnaire used is closed with a type of quantitative data that makes it possible to measure the level of student responses and perceptions regarding the use of media in the learning process. Based on the results of the analysis of the questionnaire filled out by 24 students, it was found that 66.67% of students stated that the animated video media used in learning was very interesting, while another 50% of students thought that the use of video media in the learning material for adhan and prayer was very necessary for improve their understanding. From these results, it can be concluded that the use of animated video media is very effective and interesting for students in understanding the call to prayer and prayer material, so it is recommended to carry out further development of this learning media to improve the quality of learning to be more interactive and interesting.